'You become a man in a man's world': is there discursive space for women in surgery?. Issue 12 (December 2015) - Hill, Elspeth; Solomon, Yvette; Dornan, Tim; Stalmeijer, Renée
Abstract : Context: The UK set a target of 20% of the surgical consultant workforce to be represented by women by 2009; in 2012, it remains 7%. Studies have attributed this shortfall to the nature of careers in surgery and differing career aspirations among women. Objectives: Rather than exploring barriers to participation, this study aims to explore the self‐narratives of those women who do undertake surgical careers and who do come to see themselves as surgeons. Methods: The study comprises 15 individual interviews with women in surgical careers, from those aspiring to be surgeons, to senior and retired surgeons. Data were explored using discourse analysis with a priori themes derived from the literature on women in surgery and Holland et al .'s theoretical framework of Figured Worlds . Results: Discourses of being a surgeon and discourses of being a woman, existed in competition. Female surgeons figured surgery as a career requiring 100% dedication, as they did motherhood, although the demands of the two roles differed and consequently the roles were not discursively compatible. Many related powerfully negative experiences in which their gender had marked them out as 'other' within surgery. Women described how they were expected to show masculine traits as surgeons and the ways to consequently become legitimate in the surgical world as a 'woman surgeon'. They found creative ways to articulate how women in general, and feminine qualities in particular, enhanced surgery. Finally, some women engaged in identity work, termed 'world making', – the creative orchestration of discourses of surgeonhood and motherhood to be mutually sustaining. Conclusions: There is little discursive space in which to be both a successful woman and a successful surgeon. Those who combine these roles must either be innovative in refiguring what it means to be a woman or what it means to be a surgeon, or they must author a new space for themselves, a powerful discursive process termed 'world making'. Abstract : Discuss ideas arising from the article athttp://www.mededuc.com discuss.